Interruption of capsule production in Streptococcus pneumonia serotype 3 by insertion of transposon Tn916. - Watson, D A (1990)
Transposon Tn916 mutagenesis was used to produce mutant strains of Streptococcus pneumoniae serotype 3 that lacked only a polysaccharide capsule. Southern blotting, DNA-DNA hybridization, and immunochemical analyses demonstrated that the presence of a single copy of Tn916 was sufficient to produce unencapsulation. The 50% lethal dose for such mutants was greater than 5 x 10(7) CFU, as opposed to a 50% lethal dose of 1 CFU for wild-type strains. These experiments outline an effective method for targeting genes in S. pneumoniae by transposon interruption and provide molecular evidence to support the longstanding hypothesis that the capsule is the principal virulence factor in this pathogen.